Suicidal behavior in a migrant majority population and impact on trends during the early Covid-19 period: a cross sectional study in Qatar - Majid AlAbdulla; Shuja Mohd Reagu; Mohamed H. M. O. Hassan; Nahid M. Elhassan; Sagda Sayed; Ibrahim Makki; Marwa Elzain; Ovais Wadoo; Rajeev Kumar (Discover Psychology, 2022)
Abstract Background Qatar is a high-income country with 90% of the population being economic migrants from low income countries. Due to this unique population composition, it has been suggested that Qatar may not follow suicide trends of high-income countries. Additionally, there is paucity of information on suicidal trends and rates due to social and cultural reasons. The Covid-19 pandemic has additionally impacted mental health of migrants differently form native Qataris. Objectives This study explores suicidal behavior trends among individuals attending the main Emergency Department in the state of Qatar for mental health emergencies. The study also compared these trends for pre-pandemic period to early post pandemic period. Methods A cross-sectional study of individuals attending the main emergency department of the country from 1st December 2019 to 30th June 2020 was carried out using a composite data collection form. This identified 799 individuals presenting with mental health emergencies. Suicidal behaviors, relevant sociodemographic data, along with factors known to be associated with suicidal behaviors were collected for this group. Results 24.9% (n = 199) of the sample presented with suicidal behaviors. Younger age (31.16 ± 9.497), current hopelessness (70; 54.7%), history of suicidal thoughts (50; 47.2%), history of suicidal attempts (43; 34.7%), history of self-harm thoughts (35; 39.3%), history of self-harm attempts (41; 37.6%) were highly significantly associated with suicidal behavior (p < 0.01). Qataris formed 27% of the group presenting with suicidal behaviors although they constitute only around 10% of the population. There was no significant change in the rate of presenting with suicidal behaviors during the early stages of the Covid-19 pandemic. Conclusions This study reports an annual incidence of suicidal behaviors in Qatar lower than that has been previously reported. The authors surmise that this may be due to improved availability and early intervention of mental health services and decreased stigma around mental health.